1997
DOI: 10.1038/sj.bjp.0701001
|View full text |Cite
|
Sign up to set email alerts
|

Tachykinin receptors in the guinea‐pig isolated oesophagus: a complex system

Abstract: 1 The tachykinin receptors mediating contraction of isolated longitudinal strips of the guinea-pig oesophageal body were characterized with substance P (SP), neurokinin A (NKA) and neurokinin B (NKB) as well as the analogues, [Sar 9 ,Met (O 2 ) 11 ]SP, [Nle 10 ]NKA(4 ± 10) and [MePhe 7 ]NKB, selective for NK 1 , NK 2 and NK 3 , receptors, respectively. Experiments were performed both in the absence and presence of a cocktail of peptidase inhibitors, captopril (1 mM), thiorphan (1 mM) and amastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Kerr et al (1997) found a pD 2 value of 7.2 for [Nle 10 ]-NKA(4 ± 10) in the guinea-pig whole oesophagus. It is suggested that this lower value, compared to that of 8.2 obtained in the current study may have resulted from the 10 fold lower concentrations of the peptidase inhibitors, thiorphan and captopril, used in that study.…”
Section: Agonist Effectsmentioning
confidence: 93%
See 4 more Smart Citations
“…Kerr et al (1997) found a pD 2 value of 7.2 for [Nle 10 ]-NKA(4 ± 10) in the guinea-pig whole oesophagus. It is suggested that this lower value, compared to that of 8.2 obtained in the current study may have resulted from the 10 fold lower concentrations of the peptidase inhibitors, thiorphan and captopril, used in that study.…”
Section: Agonist Effectsmentioning
confidence: 93%
“…The e ect of NKA was tested in the absence of peptidase inhibitors, because it has been shown that these enzyme inhibitors do not signi®cantly a ect the response to this peptide in the guinea-pig whole oesophagus preparation (Kerr et al, 1997). The e ects of senktide, which is protected from peptidases by the succinyl moiety, were also tested in the absence of peptidase inhibitors.…”
Section: Peptidase Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations